Cloning and expression analysis of the HSL gene in Whitmania pigra (Annelida: Hirudinea). Issue 1 (2nd January 2022) - Guo, Li-Yuan; Guo, Qiao-Sheng; Shi, Hong-Zhuan; Yang, Feng; Miao, Yi-Xiu
ABSTRACT: Hormone-sensitive lipase (HSL) is the rate-limiting enzyme of lipolysis, which has a certain effect on the reproductive development of parthenogens. To study the effect of HSL on gonad development in Whitmania pigra, a synchronous hermaphrodite, the Whitmania pigra HSL gene was cloned. The cloned Wpi-hsl has a total length of 2492 bp, and the ORF encodes a protein of 787 aa. It is predicted that the Wpi-HSL protein has 98 phosphorylation modification sites on serine, threonine and tyrosine residues. Domain prediction and multiple sequence comparison revealed that Wpi-HSL contains 3 HSL conserved domains, which are closely related to Helobdella robusta, and the amino acid sequence similarity and sequence identity are 49% and 39%, respectively. Fluorescence quantitative PCR results showed that in the mature period, the expression of Wpi-hsl in the male gonads was significantly higher than that in the female gonads. Wpi-hsl may play an important role in the development of W. pigra, especially the development of male gonads. The results of our study provide references for not only further research on leech gonadal development but also the study of reproductive development mechanisms.